Towards a Transformation of Advertising. Thoughts on the Alleged Superficiality Given to Advertising Throughout Time - Novoa-Montoya, Andrés (2016)
Social imaginaries built around Advertising, from the audience and from advertising itself, undermine scopes, approaches and functions they have into society. This paper aims to present a critical and reflexive analysis of the Advertising’s current role in society, searching for a transformative structure that reveals the importance of research, both in academics and in the creative process behind successful advertising campaigns. It is an invitation to see Advertising with a less reductive view, as a discipline with its own knowledge and deep connections with social and human sciences that goes beyond a simple professional point of view, but does not ignore or exceed it.